Growth Rate of (Oreochromis sp) Saline Tilapia Seeds Cultured in Biofloc System using Fermented Vegetable Waste Feed (Torani Journal of Fisheries and Marine Science, 2022)
This study aims to determine the growth rate of Salin tilapia (Oreochromis sp.) which is cultivated in a biofloc system using fermented vegetable waste feed. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications and the feed used was fermented vegetable waste with different doses of prebiotics, treatment A Control, B 30 ml/kg, C 40 ml/kg, and D 50 ml /kg. The results showed that the feeding of fermented vegetable waste had a significantly different effect (P